2001
DOI: 10.2175/106143001x138714
|View full text |Cite
|
Sign up to set email alerts
|

Fate and Toxicity of Aircraft Deicing Fluid Additives Through Anaerobic Digestion

Abstract: Benzotriazole derivatives are widely used corrosion inhibitors and their fate during wastewater treatment processes is unknown. The purpose of this research was to study the toxic effects and fate of the two commercially significant benzotriazole isomers used in aircraft deicing fluids (4-, and 5-, methylbenzotriazole [MeBT]) during anaerobic digestion. Experiments were executed in microcosms using mesophilic anaerobic biomass co-digesting wastewater sludge and propylene glycol. Sorption of MeBT to digesting s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
46
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(52 citation statements)
references
References 24 publications
6
46
0
Order By: Relevance
“…Previous studies have shown that BTs in the environment are quite resistant to microbial degradation (Breedveld et al, 2003;Gruden et al, 2001;Weiss et al, 2006). BTs are reported to have low to moderate elimination rates (11-74%) in conventional wastewater treatment plants (Voutsa et al, 2006;Weiss et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that BTs in the environment are quite resistant to microbial degradation (Breedveld et al, 2003;Gruden et al, 2001;Weiss et al, 2006). BTs are reported to have low to moderate elimination rates (11-74%) in conventional wastewater treatment plants (Voutsa et al, 2006;Weiss et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…BTs in the environment are quite resistant to microbial degradation (Gruden et al, 2001;Weiss et al, 2006). With the exception of a few reports on removal of BTs in conventional WWTPs, very little is known about their biodegradation potential and mechanisms under environmental conditions (Breedveld et al, 2003;Weiss et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Although BT is known to be quite resistant to microbial degradation, [17] it is highly photochemically sensitive. [18] UV photolysis has been applied as an advanced wastewater treatment technology to remove some trace organic contaminants in waste streams.…”
mentioning
confidence: 99%